Pastoral systems research in sub-Saharan Africa - Stewart, R.A. (International Livestock Centre for Africa, 1983)
Presents a collection of conference papers defining pastoral systems research; the survey and diagnostic phase of pastoral systems research; ILCA's experience in remote sensing techniques and aerial surveys; survey of vegetation resources; livestock productivity and animal nutrition; pastoral production strategies, wealth effects, household studies, and labour data collection as well as livestock marketing studies. Includes papers on possibilities for improvement in pastoral production; procedures relevant to pastoral systems research, and findings of case studies from Nigeria and Niger highlighting the experimental and testing procedures relevant to pastoral systems research.